Pengaruh Budaya Organisasi Dan Motivasi Kerja Terhadap Produktivitas Kerja Guru SMP Di Kecamatan Rawamerta Kabupaten Karawang Jawa Barat - irfan mujahidin; Syamsudin Kastoer (Thawalib: Jurnal Kependidikan Islam, 2021)
This research aims to investigate the effect of organizational culture and job motivation as independent variables toward the teacher’s work productivity of state junior high school teachers as dependent variable, both individually and collectively. Among 60 senior high school  teachers were surveyed and 52 respondent were selected as samples for the research. Normality, homogenity,linearity, multiple regression,and multiple correlation are several data analysis method that were used in this research using the SPPS 21.0 program for Windows.The result of this research imply that: Firstl,  a positive and significant effect was found Teacher’s Work Productivity by Organizational Culture and Job Motivation collectivelly and expressed in coefficient correlation  ry1.2 = 0,672 (a = 0,05) and regression equation as Y = 43,0378 + 0,603 X1  +  0,273 X2 and  determination coefficient is  r2y1.2 = 0,451.Secondly, a positive and significant corelation was found Organizational Culture toward Teacher’s Work Productivity  can be found and  expressed in hypothesis testing that the value of Sig = 0.000 and t = 5.767, while t table = 2.021. Because the value of Sig <0.05 and tcount > ttable, H0 is rejected, it means that there is a significant effect of the independent variable X1 (organizational culture) on the dependent variable Y (Teacher’s Work Productivity). Thirdly, this research also found that there is a positive and significant corelation was found Job Motivation toward Teacher’s Work Productivity can be found and  expressed in  the hypothesis testing, it was obtained that the value of Sig = 0.000 and tcount = 3.881, while ttable = 2.021. The value of Sig <0.05 and tcount > ttable, so H0 is rejected, it means that there is a significant effect of the independent variable X2 (job motivation) toward the dependent variable Y (Teacher’s Work Productivity). According to result of this research that improvement of Teacher’s Work Productivity  can be in creased by Organizationalal Culture and Job Motivation interest.